Exploring Traditional and Emerging Biomarkers in Type 2 Diabetes Mellitus: A Comprehensive Overview of Diagnostic and Prognostic Tools - Mohammed, Chinar Mustafa; Ahmed, Dilveen Y.; Naif, Rondik O. (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
Type 2 Diabetes Mellitus is Among the most prevalent and globally widespread metabolic disorders. Though it has been associated with elderly people, recently the prevalence of younger individuals affected with T2DM has significantly increased. Currently, there is a broad range of diabetic biomarkers with those extensively used in clinical medicine such as HbA1c and those on ongoing research. Despite the competence of current diabetes biomarkers, they all display limitations in terms of accuracy and convenience, for this reason, there is a continuous urge to discover reliable, precise, and conventional biomarkers for early diagnosis and treatment of patients. This review encompasses a comprehensive background on both traditional as well as novel T2DM biomarkers therefore guides future research.